Designing an assistive & accessible schedule - Lawrence, Jonathan; Solibi, Thomas (My University, 2023)
This master thesis project aims to focus on the topic of designing an accessible schedule for people with intellectual disabilities. This project was carried out at the request of Grunden Media. Grunden Media has requested a prototype and accompanying usability study to determine what should be considered when designing a smartphone application schedule. The user group are the participants at Grunden who will use the application to view their daily schedules. The research question for this thesis is: What are the best practices when designing a digital schedule for people with varying cognitive and motor skills? Both literature studies and interviews were conducted with employees and participants at Grunden Media throughout the design process to gather insights and evaluate the designed prototypes and provide an answer to the research question. The research and evaluation resulted in the presented best practices to consider when designing for intellectual disabilities. These include following guidelines such as WCAG, learning from people with disabilities by involving them in the process and providing alternatives to avoid exclusion when possible.
Keywords: User experience; user-centred design; interaction design; accessibility; intellectual disability; engineering; project; thesis